2019
DOI: 10.1186/s12909-019-1852-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of smart phone application use as continuing medical education method in pediatric oral health care: a randomized trial

Abstract: BackgroundContinuing education aims at assisting physicians to maintain competency and expose them to emerging issues in their field. Over the last decade, approaches to the delivery of educational content have changed dramatically as medical education at all levels is now benefitting from the use of web-based content and applications for mobile devices. The aim of the present study is to investigate through a randomized trial the effectiveness of a smart phone application to increase public health service phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
3
17
0
1
Order By: Relevance
“…For online teaching to be successful and meaningful, the educational resources must be well structured, and the learning experiences must be intended to promote engaging interaction for learners. [ 1 ] Online learning or distance education was introduced in developed countries early, however lower middle-income countries have migrated to e-learning technology during COVID-19 breakdown, when many universities were shut down, and online education through digital technology was initiated. The World Economic Forum has reported that many universities in developed countries have adopted the transition to online teaching, smoothly and successfully offering more than 5000 online courses.…”
mentioning
confidence: 99%
“…For online teaching to be successful and meaningful, the educational resources must be well structured, and the learning experiences must be intended to promote engaging interaction for learners. [ 1 ] Online learning or distance education was introduced in developed countries early, however lower middle-income countries have migrated to e-learning technology during COVID-19 breakdown, when many universities were shut down, and online education through digital technology was initiated. The World Economic Forum has reported that many universities in developed countries have adopted the transition to online teaching, smoothly and successfully offering more than 5000 online courses.…”
mentioning
confidence: 99%
“…In the current study, the resident physicians did not show much inclination towards using live casts, or electronic conferencing, particularly for workshops, courses or inter departmental activities. which has shown to improve knowledge, attitude and practice of physicians [28].This trend has been reported earlier by students from a university in Najran, Saudi Arabia, who reported that 97% of them have computer and internet access, yet 73% opted for conventional learning methods. [29] One of the main findings of this study is that the main barrier against attending all forms of CME was being busy, although it was higher for self-reading than contact CME like attending lectures and seminar courses.…”
Section: Resultsmentioning
confidence: 55%
“…This is an interesting nding, considering that internet penetration rate in KSA at 93.3%, is among the highest globally [29]. This highlights under-usage of an effective resource friendly learning method, which has shown to improve knowledge, attitude and practice of physicians [30].This trend has been reported earlier by students from a university in Najran, Saudi Arabia, who reported that 97% of them have computer and internet access, yet 73% opted for conventional learning methods. [31] One of the main ndings of this study is that the main barrier against attending all forms of CME was being busy, although it was higher for self-reading than contact CME like attending lectures and seminar courses.…”
Section: Resultsmentioning
confidence: 99%